Saccharomyces cerevisiae as a Model for Screening the Effects of Volatile Organic Compounds - U. Morath, Shannon; E. Boland, Caitlin; W. Bennett, Joan (Current Biotechnology, 2017)
Background: Volatile organic compounds (VOCs) are gaseous at room temperature, readily dissipate throughout the environment, and may be of anthropogenic or biogenic origin. Despite an increasing scientific interest in the role VOCs play in interspecific interactions, there remains a limited understanding of the impact of VOCs on fungi living in a shared space. Objective: In this study, we aimed to determine the sensitivity of the model organism Saccharomyces cerevisiae (yeast) in response to exposure to VOCs, collectively or singularly produced by bacteria, fungi, plants, and in industrial processes, and containing various chemical functional groups. Methods: Using a serial dilution spot assay with yeast wild-type strain BY4741, 27 compounds were screened at 10 ppm for 48 hr to determine their impact on yeast growth. Results: We found that gas-phase formaldehyde, three common microbial VOCs, 1-octanol, 1-octen-3- one, and trans-2-octenal, and a common plant VOC, trans-2-hexen-1-al, completely inhibited yeast growth at 10 ppm, while 1-octen-3-ol, 2-methylpropanal and benzene were significantly limiting. Additionally, we identified 2 common microbial VOCs, 3-methyl-1-butanol and 3-octanone, that significantly increased yeast growth. Conclusion: This study demonstrates that yeast provides a useful tool to study the effect of VOCs in shared spaces, serving as a model for other eukaryotic species in the built environment.
Keywords: built environment